Neutralization capacity of highly divergent type 2 vaccine-derived polioviruses from immunodeficient patients. Issue 14 (23rd March 2020) - McDonald, Sharla L.; Weldon, William C.; Wei, Ling; Chen, Qi; Shaw, Jing; Zhao, Kun; Jorba, Jaume; Kew, Olen M.; Pallansch, Mark A.; Burns, Cara C.; Steven Oberste, M.
Abstract: The use of the oral poliovirus vaccine (OPV) in developing countries has reduced the incidence of poliomyelitis by >99% since 1988 and is the primary tool for global polio eradication. Spontaneous reversions of the vaccine virus to a neurovirulent form can impede this effort. In persons with primary B-cell immunodeficiencies, exposure to OPV can result in chronic infection, mutation, and excretion of immunodeficiency-associated vaccine-derived polioviruses, (iVDPVs). These iVDPVs may have the potential for transmission in a susceptible population and cause paralysis. The extent to which sera from OPV recipients are able to neutralize iVDPVs with varying degrees of antigenic site substitutions is investigated here. We tested sera from a population immunized with a combination vaccine schedule (both OPV and inactivated polio vaccine) against a panel of iVDPVs and found that increases in amino acid substitution in the P1 capsid protein resulted in a decrease in the neutralizing capacity of the sera. This study underscores the importance of maintaining high vaccine coverage in areas of OPV use as well as active surveillance of those known to be immunocompromised.